An assessment of tourist knowledge and awareness level towards the environment in Tunku Abdul Rahman Park, Malaysia / Nasrulhakim Maidin, B. Mabel Manjaji-Matsumoto and M. Rafiee Asdari - Maidin, Nasrulhakim; Manjaji-Matsumoto, B. Mabel; Asdari, M. Rafiee (Universiti Teknologi MARA, Perak, 2021)
Tunku Abdul Rahman Park (TARP) is the first Marine Protected Area gazetted in Sabah, Malaysia in 1974. It is also one of the most famous tourist destinations in Sabah which experiences a high anthropogenic disturbance that could create major damage in the long run if not properly managed. TARP has been flooded by tourists receiving more than 500,000 tourists in 2018 and 2019. It is clear that tourism activity in TARP is one of the major contributions to anthropogenic disturbance. Therefore, it is essential for tourists to have a high level of awareness to conduct sustainable and eco-friendly tourism activity. In this study, we assessed the level of awareness and knowledge of the marine environment among tourists in TARP. Briefings by tour guides or companies were also assessed. Overall, results showed a low awareness level among tourists in TARP. This is somehow related to the fact that the briefing score by tour companies was low and only focused on promoting their company. TARP authority should implement a standard 5-minute video on the marine environment and assign more signage on the island in an effort to raise awareness among tourists.